Towards Reformulation of Waqf: An Indonesians Discourse - Sofiandi Sofiandi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
In terms of history, waqf has played a very important role in improving the economic life of Muslims in all parts of the world. The main function of waqf which is closely related to worship practices must be followed by various and creative efforts in operating the economic functions it contains. The modern paradigm of management of waqf assets productively demands a more advanced management mechanism with all forms and spaces to innovate which ultimate goal is to carry out and run the economic functions. Some Muslim countries have succeeded in doing this. However, Indonesia, which has the most Muslim population in the world, does not benefit significantly from waqf. This article aims to offer a reformulation landscape on the concept of waqf that can be applied in Indonesia.